Using artificial intelligence as a revitalisation tool for the sustainability of endangered languages: Young linguists' voices - Humaira Irfan; Maya Khemlani David; Syeda Rabia Tahir; Nurah Alfares (Universitas Syiah Kuala, 2026)
This study explored the transformative potential of artificial intelligence (AI) powered language learning approaches in preserving endangered languages and maintaining linguistic and cultural diversity in Pakistan for sustainable pedagogy and acquisition of these languages. As emphasised by UNESCO, nearly half of the world's 7,000 languages are at risk of extinction, with more than 200 lost between 1950 and 2010, reflecting an alarming decline in global cultural and linguistic heritage. Employing a qualitative research design, the investigation captured the perspectives of 20 young linguists who participated in an open-ended survey. They currently teach at public and private universities in Lahore, Punjab, Pakistan, representing a small but information-rich group engaged in academic and applied linguistic work. Data were collected through an open-ended survey instrument consisting of two sections: demographic information (Part A) and participants’ views on endangered languages and AI (Part B). The results revealed that participants viewed AI as a catalyst for revitalising endangered languages through the creation, conception, and development of language instructional materials, including articles, narratives, and interactive learning resources in endangered languages. They also highlighted the value of AI-driven applications in providing immersive, collaborative, and language-enhancing tools, such as innovative language lessons, exercises, quizzes, and gamified activities personalised to regional vernaculars. Furthermore, they visualised that any developments in machine learning, natural language processing, real-time translation, speech recognition, and context-aware AI systems, particularly those sensitive to dialectal variation, will play a pivotal role in the sustainable preservation of endangered languages, especially within the educational and language-teaching contexts of Pakistan.